2002
DOI: 10.2320/matertrans.43.1533
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a TiO<SUB>2</SUB> Film Coated Si Device for Photo-Decomposition of Water by CVD Method Using Ti(OPr<SUP>i</SUP>)<SUB>4</SUB>

Abstract: Growth of a TiO 2 film on a Si wafer by CVD method was studied for a new design of chemically stable device which is useful in the visible region and increases the efficiency of the photocatalytic decomposition process of water. This design is made up of a monolithic structure of a TiO 2 thin film and a Si solar cell. The TiO 2 film was deposited on a Si substrate by the vapor phase reaction of Ti(OPr i ) 4 with water at temperatures from room temperature to 473 K. At room temperature, a rough TiO 2 film with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…As far as the CVD of TiO 2 films is concerned, the reaction of TTIP with H 2 O to form TiO 2 , Ti(OnormalC3normalH7)4(g)+2normalH2O(g)TinormalO2(s)+4normalC3normalH7OH(g), can occur at room temperature . TiO 2 film prepared by CVD based on the hydrolysis reaction at room temperature has already been reported, however, to the best of our knowledge, that under atmospheric pressure on a moving substrate has not yet been reported. Herein, facile and fast deposition of TiO 2 film on a moving substrate under atmospheric pressure and at room temperature using TTIP and H 2 O as CVD sources is reported.…”
Section: Introductionmentioning
confidence: 98%
“…As far as the CVD of TiO 2 films is concerned, the reaction of TTIP with H 2 O to form TiO 2 , Ti(OnormalC3normalH7)4(g)+2normalH2O(g)TinormalO2(s)+4normalC3normalH7OH(g), can occur at room temperature . TiO 2 film prepared by CVD based on the hydrolysis reaction at room temperature has already been reported, however, to the best of our knowledge, that under atmospheric pressure on a moving substrate has not yet been reported. Herein, facile and fast deposition of TiO 2 film on a moving substrate under atmospheric pressure and at room temperature using TTIP and H 2 O as CVD sources is reported.…”
Section: Introductionmentioning
confidence: 98%
“…10) The main difference between the TNA-based and TiO 2 lm based TiO 2 /water SLHJ UV-PDs is that the latter used an active layer of TiO 2 lm grown by atomic layer deposition (ALD), 19) while the former used a TNA active layer grown by a non-vacuum, low-cost hydrothermal process. The active area of the device for UV-light detection is about 0.196 cm 2 .…”
Section: Fabrication and Characterization Of Tio 2 Nanorodmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) is a nontoxic and low-cost wide bandgap semiconductor. It has been widely studied as a key material for fabricating photocatalytic water-splitting devices, 1,2) dye-sensitized solar cells (DSSCs), 3,4) lithium-ion batteries, 5,6) gas sensors, 7,8) and ultraviolet photo-detectors (UV-PDs). 9,10) In order to improve the performances of devices, TiO 2 nanomaterials such as TiO 2 nanoparticles, 11) TiO 2 hollow nanospheres, 12) TiO 2 nanotubes, 13) TiO 2 nanowires, 14) and TiO 2 nanorods 15) constructed nanomaterials have been extensively investigated during the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…A number of methods have been studied to produce porous TiO 2 electrodes, such as spin-coating, 7) spray coating, 2,8) electrospinning 1,3,9,10) screen-printing, 4) sputtering, 5) and chemical vapor deposition. 6) Our previous studies revealed that DSSCs consisting of a TiO 2 nanorod layer as the electrode showed an energy conversion efficiency of 5.07%. 8) The TiO 2 nanorod layer prepared by spray coating has good adhesion on fluorine-doped tin oxide glass (FTO) substrates.…”
Section: Introductionmentioning
confidence: 97%
“…This is because the DSSCs have low cost and reasonably high efficiency. [1][2][3][4][5][6][7] The DSSC consists of a dye-sensitized porous electrode made of TiO 2 nanomaterials, a platinum counter electrode, and an electrolyte solution between the electrodes. The dye-sensitized TiO 2 electrode should have a high surface area in order to enhance the efficient light-to-energy conversion of DSSCs.…”
Section: Introductionmentioning
confidence: 99%